LEADERSHIP STYLE MANAGEMENT IN ISLAMIC BOARDING SCHOOL: META ANALYSIS AND SYSTEMIC REVIEW - Muttaqin, Zainal; Tarihoran, Naf’an; Nugraha, Enung (Yayasan Education and Social Center, 2025)
This research aims to analyze the influence of various leadership styles on Islamic boarding school management through a meta-analysis and systematic review approach. In this research, data was collected from various studies related to transformational, transactional, charismatic, participative and autocratic leadership styles applied in Islamic boarding schools. The results of the analysis show that the transformational leadership style has proven to be the most effective in increasing students' motivation and self-development, while the transactional style focuses more on discipline and operational efficiency. The charismatic style is able to motivate students, but needs to be balanced with the development of other aspects of leadership to avoid excessive dependence. The participatory style increases students' sense of responsibility and loyalty, although it requires more time and effort to implement. An autocratic leadership style is more effective in contexts that require strict structure and discipline, but can reduce creativity and initiative. This research concludes that an adaptive combination of various leadership styles is needed to create an environment that is conducive to the development of students and improve the performance of Islamic boarding schools as a whole.